Common maternal infections during pregnancy and childhood leukaemia in the offspring: findings from six international birth cohorts. (14th September 2021) - He, Jian-Rong; Hirst, Jane E; Tikellis, Gabriella; Phillips, Gary S; Ramakrishnan, Rema; Paltiel, Ora; Ponsonby, Anne-Louise; Klebanoff, Mark; Olsen, Jørn; Murphy, Michael F G; Håberg, Siri E; Lemeshow, Stanley; et al.
Abstract: Background: Previous epidemiological studies have found positive associations between maternal infections and childhood leukaemia; however, evidence from prospective cohort studies is scarce. We aimed to examine the associations using large-scale prospective data. Methods: Data were pooled from six population-based birth cohorts in Australia, Denmark, Israel, Norway, the UK and the USA (recruitment 1950s-2000s). Primary outcomes were any childhood leukaemia and acute lymphoblastic leukaemia (ALL); secondary outcomes were acute myeloid leukaemia (AML) and any childhood cancer. Exposures included maternal self-reported infections [influenza-like illness, common cold, any respiratory tract infection, vaginal thrush, vaginal infections and urinary tract infection (including cystitis)] and infection-associated symptoms (fever and diarrhoea) during pregnancy. Covariate-adjusted hazard ratio (HR) and 95% confidence interval (CI) were estimated using multilevel Cox models. Results: Among 312 879 children with a median follow-up of 13.6 years, 167 leukaemias, including 129 ALL and 33 AML, were identified. Maternal urinary tract infection was associated with increased risk of any leukaemia [HR (95% CI) 1.68 (1.10–2.58)] and subtypes ALL [1.49 (0.87–2.56)] and AML [2.70 ([0.93–7.86)], but not with any cancer [1.13 (0.85–1.51)]. Respiratory tract infection was associated with increased risk of any leukaemia [1.57 (1.06–2.34)], ALL [1.43 (0.94–2.19)], AML [2.37 (1.10–5.12)] and any cancer [1.33 (1.09–1.63)]; influenza-like illness showed a similar pattern but with less precise estimates. There was no evidence of a link between other infections and any outcomes. Conclusions: Urinary tract and respiratory tract infections during pregnancy may be associated with childhood leukaemia, but the absolute risk is small given the rarity of the outcome.